THE NEUROPROTECTION CAUSED BY PHYTOCANABINOIDS, THEIR EFFECTS AND THEIR APPLICABILITY IN BRAZIL - Eduarda Serafim Crispim, Maria; de Ávila Lins da Cunha Lima, Juliana; Braga Santos, Gabriela; Ribeiro Coutinho de Mendonça Furtado, Flaviana; Ribeiro Coutinho de Mendonça Furtado, Beatriz (Health and Society, 2022)
Introduction: The endocannabinoid system is composed of cannabinoid receptors type 1 (CB1) and type 2, their endogenous agonists, anandamide endocannabinoids and 2-aaquidonoilglycerol (2-AG). It is assumed that 2-AG is the binding receptor of cannabidioids to the Central Nervous System. CB1 inhibits the release of GABA and glutamate from pre-sinaptic terminals, being responsible for the ability to modulate neurotransmission as a mechanism of neuroprotection of CB1 against excitotoxicity. This action provides a good justification for such mechanisms to be investigated as therapeutic targets for severe neurodegenerative diseases, including Alzheimer’s disease, Huntington’s disease, and Parkinson’s disease. Development: Cannabidiol is more related to neuroprotective activity, tolerable at higher doses and less cardiovascular and psychological risks, THC to psychotropic effects, since there are medications that contain both substances, there should be a control of its prescription and care for self-medication. Final Considerations: Although we know that cannabidiol has an impact and medicinal value, more studies need to be done, and there should be greater rigor on composition and concentrations, due to the high power of interaction with other substances and their toxic power when used erroneously. Finally, it is known of its beneficial potential for various neurodegenerative diseases.